Trends and determinants of total factor productivity in Rice (Oryza sativa) and Wheat (Triticum aestivum) - R H, ANKHILA; SINGH, ALKA; SINGH, D R; KUMAR, PRABHAKAR; B, BHARGAVI (The Indian Journal of Agricultural Sciences, 2022)
The study estimates total factor productivity (TFP) in rice (Oryza sativa L.) and wheat (Triticum aestivum L.) which form the mainstay of food security in India. The study period is 25 years from 1991–92 to 2015–16, secondary data from 12 major rice and wheat producing states was collected from Directorate of Economics and Statistics (DES). Results depict declining mean TFP for both rice and wheat in the period II (2002–2015) compared to period I (1991–2001) of study. Major producing states have been facing stagnation in productivity and the results also confirm the proposition that technical efficiency could not catch up with the technical progress in both wheat and rice cultivation. Hence, the results confirm that the TFP change was associated more with technical change than with efficiency change in all the states during both the study periods. Thus, the results conclude that the agricultural development strategy has to pay increased attention towards the factors that could influence the efficiency as well along with the factors that result in technical progress especially in case of rice and wheat which constitute the Indian food security basket.